Effects of short-term exercise and endurance training on skeletal muscle mitochondria damage induced by particular matter, atmospherically relevant artificial PM2.5 - Liu, Wenduo; Wang, Zilin; Gu, Yu; So, Han-Sol; Kook, Sung-Ho; Park, Yoonjung; Kim, Sang Hyun (Frontiers in Public Health, 2024)
Introduction: This study aimed to investigate the potential of short-term aerobic exercise to mitigate skeletal muscle mitochondrial damage following ambient PM2.5 exposure, and how 12 weeks of endurance training can enhance aerobic fitness to protect against such damage. Methods: Twenty-four male C57BL/6J mice were split into sedentary (SED, n=12) and endurance training (ETR, n=12) groups. The ETR group underwent 12 weeks of training (10-15m/min, 60min/day, 4 times/week), confirmed by an Endurance Exercise Capacity (EEC) test. Post-initial training, the SED group was further divided into SSED (SED and sedentary, n=6) and SPE (SED and PM2.5 + Exercise, n=6). Similarly, the ETR group was divided into EEX (ETR and Exercise, n=6) and EPE (ETR and PM2.5 + Exercise, n=6). These groups underwent one week of atmospherically relevant artificial PM2.5 exposure and treadmill running (3 times/week). Following treatments, an EEC test was conducted, and mice were sacrificed for blood and skeletal muscle extraction. Blood samples were analyzed for oxidative stress indicators, while skeletal muscles were assessed for mitochondrial oxidative metabolism, antioxidant capacity, and mitochondrial damage using western blot and transmission electron microscopy (TEM). Results: After 12 weeks of endurance training, the EEC significantly increased (p < 0.000) in the ETR group compared to the SED group. Following a one-week comparison among the four groups with atmospherically relevant artificial PM2.5 exposure and exercise treatment post-endurance training, the EEX group showed improvements in EEC, oxidative metabolism, mitochondrial dynamics, and antioxidant functions. Conversely, these factors decreased in the EPE group compared to the EEX. Additionally, within the SPE group, exercise effects were evident in HK2, LDH, SOD2, and GPX4, while no impact of short-term exercise was observed in all other factors. TEM images revealed no evidence of mitochondrial damage in both the SED and EEX groups, while the majority of mitochondria were damaged in the SPE group. The EPE group also exhibited damaged mitochondria, although significantly less than the SPE group. Atmospherically relevant artificial PM2.5 exposure can elevate oxidative stress, potentially disrupting the benefits of short-term endurance exercise and leading to mitochondrial damage. Nonetheless, increased aerobic fitness through endurance training can mitigate PM2.5-induced mitochondrial damage.